The role of pondscapes in supporting identities - Lluís Benejam; Jacques-Aristide Perrin; Malgorzata Blicharska; Sandra Brucet; Deniz Başoğlu; Meryem Beklioglu; Aurelie Boissezon; Dani Boix; Maite Colina; Thomas Alexander Davidson; Pieter Lemmens; Alejandro López-de Sancha; et al. (Hydrobiologia, 2026)
This study investigates how pondscapes, networks of ponds, and their surrounding environments contribute to supporting identities across diverse cultural contexts. Supporting identities is a non-material Nature’s Contribution to People referring to people’s sense of place, belonging and connection to nature. We draw on data on landscape features from 17 pondscapes across eight countries in Europe and South America, along with over 700 questionnaire responses. We assessed whether certain landscape features are associated with the perceived delivery of supporting identities and examined how personal characteristics, individual perspectives, and engagement in different activities shape people’s perceptions. Our findings indicate that the perceived delivery of supporting identities emerges from a combination of social and ecological factors rather than from landscape features alone. Although pondscape characteristics showed weak direct effects, pondscapes in warmer climates and with a higher proportion of natural land cover might be associated with a stronger sense of identity. In addition, a strong personal connection to nature and engagement in nature-based activities (wildlife watching, picnicking, hunting), were key pathways shaping perceptions, highlighting that identity-related benefits are context dependent and socially mediated. By integrating ecological and social dimensions, our study highlights the importance of incorporating non-material values into conservation and landscape management strategies.

Larger crustacean zooplankton thrive at lower temperatures and under reduced predation in pond ecosystems - Katterine Rincón-Palau; Anna Badosa; Feride Avci; Mireia Bartrons; Meryem Beklioglu; Dani Boix; Maria Cuenca-Cambronero; Thomas A. Davidson; Gissell Lacerot; Pieter Lemmens; Luis Martín; Mariana Meerhoff; et al. (Hydrobiologia, 2026)
Body size is a fundamental trait influencing ecological functions, trophic dynamics, and organismal fitness across ecosystems. However, the environmental drivers shaping body size patterns in pond ecosystems across broad spatial scales remain poorly defined. In this study, we assessed the main determinants of body size in cladocerans and copepods, key crustacean zooplankton groups, across 168 ponds including regions in Europe, Asia, and South America. We assess how temperature and latitudinal variation, food availability, and predation influence mean and maximum crustacean body sizes in zooplankton taxa. Using linear mixed models, we identified annual temperature and predation pressure as the strongest predictors of body sizes. Body size increased with lower temperature for both taxa, supporting the temperature-size rule. Fish presence was associated with smaller body sizes for both taxa, while copepod size metrics were additionally influenced by pond morphometry, showing a negative relationship with depth and a positive association with area. These findings suggest temperature and predation pressure act as major selective forces shaping crustacean body size in pond ecosystems. Understanding these patterns is essential for predicting how crustacean communities and processes they mediate may respond to ongoing climate warming, particularly in small-shallow freshwater ecosystems highly sensitive to environmental change.

Energy‐based top‐down and bottom‐up relationships between fish community energy demand or production and phytoplankton across lakes at a continental scale - Mireia Bartrons; Thomas Mehner; Christine Argillier; Meryem Beklioglu; Petr Blabolil; Trygve Hesthagen; Kerstin Holmgren; Erik Jeppesen; Teet Krause; Samo Podgornik; Pietro Volta; Ian J. Winfield; et al. (Limnology and Oceanography, 2020)
Fish community feeding and production rates may differ between lakes despite similar fish biomass levels because of differences in size structure and local temperature. Therefore, across‐lake comparisons of the strength and direction of top‐down and bottom‐up fish–phytoplankton relationships should consider these factors. We used the metabolic theory of ecology to calculate size‐ and temperature‐corrected community energy demand (CED om ) and community production (CP) of omnivorous fishes in 227 European lakes from major habitat types (MHTs) of polar freshwaters, temperate floodplain rivers and wetlands, and temperate coastal rivers. We related CED om with total phosphorus (TP)‐corrected chlorophyll a (Chl a ) concentrations to evaluate a potential top‐down directed trophic cascade from fish to phytoplankton. Furthermore, we related Chl a with CP to demonstrate potential bottom‐up effects of phytoplankton on fish. For both analyses, we added the CED of piscivorous fishes (CED pi ) as a predictor to account for potential predation effects on the omnivorous fish community. CED om was weakly positively related with TP‐corrected Chl a , but the strength of the relationship differed between MHTs. In contrast, CP was consistently positively related with Chl a in the entire dataset. CED pi did not contribute to top‐down or bottom‐up relationships. The application of metabolic variables characterizing fish community feeding and production rates makes these results robust because the approach accounted for the usually neglected effects of fish size and temperature in across‐lake comparisons. Our results suggest that bottom‐up effects from phytoplankton on fish secondary production in lakes are substantially stronger than top‐down effects from fish on phytoplankton biomass.

Non-native Fish Occurrence and Biomass in 1943 Western Palearctic Lakes and Reservoirs and their Abiotic and Biotic Correlates - Carolina Trochine; Sandra Brucet; Christine Argillier; Ignasi Arranz; Meryem Beklioglu; Lluís Benejam; Teresa Ferreira; Trygve Hesthagen; Kerstin Holmgren; Erik Jeppesen; Fiona Kelly; Teet Krause; et al. (Ecosystems, 2018)

Impacts of salinity and fish-exuded kairomone on the survival and macromolecular profile of Daphnia pulex - Gizem Bezirci; Sara B. Akkas; Karsten Rinke; Feriha Yildirim; Zeynep Kalaylioglu; Feride Severcan; Meryem Beklioglu (Ecotoxicology, 2012)

Climate change effects on nitrogen loading from cultivated catchments in Europe: implications for nitrogen retention, ecological state of lakes and adaptation - Erik Jeppesen; Brian Kronvang; Jørgen E. Olesen; Joachim Audet; Martin Søndergaard; Carl C. Hoffmann; Hans E. Andersen; Torben L. Lauridsen; Lone Liboriussen; Søren E. Larsen; Meryem Beklioglu; Mariana Meerhoff; et al. (Hydrobiologia, 2011)

Preface - Mariana Meerhoff; Meryem Beklioglu; Romi Burks; Felipe García-Rodríguez; Néstor Mazzeo; Brian Moss (Hydrobiologia, 2010)

Drought-induced changes in nutrient concentrations and retention in two shallow Mediterranean lakes subjected to different degrees of management - Arda Özen; Burcu Karapınar; İsmail Kucuk; Erik Jeppesen; Meryem Beklioglu (Hydrobiologia, 2010)

Effects of 4-nonylphenol, fish predation and food availability on survival and life history traits of Daphnia magna straus - Meryem Beklioglu; S. Banu Akkas; H. Elif Ozcan; Gizem Bezirci; Inci Togan (Ecotoxicology, 2010)

Molecular approach to the chemical characterization of fish-exuded kairomone: a Fourier transform infrared spectroscopic study - Sara B. Akkas; Ayse O. Kepenek; Meryem Beklioglu; Feride Severcan (Aquatic Sciences, 2010)

Impact of food concentration on diel vertical migration behaviour of Daphnia pulex under fish predation risk - Meryem Beklioglu; Ayse Gul Gozen; Feriha Yıldırım; Pelin Zorlu; Sertac Onde (Hydrobiologia, 2008)

State of the art in the functioning of shallow Mediterranean lakes: workshop conclusions - Meryem Beklioglu; Susana Romo; Ifigenia Kagalou; Xavier Quintana; Eloy Bécares (Hydrobiologia, 2007)

Effects of waterfowl, large fish and periphyton on the spring growth of Potamogeton pectinatus L. in Lake Mogan, Turkey - Håkan Sandsten; Meryem Beklioglu; Özlem Ince (Hydrobiologia, 2005)

Absence of typical diel vertical migration in Daphnia: varying role of water clarity, food, and dissolved oxygen in Lake Eymir, Turkey - Cagri B. Muluk; Meryem Beklioglu (Hydrobiologia, 2005)

The role of water-level fluctuations in shallow lake ecosystems – workshop conclusions - Hugo Coops; Meryem Beklioglu; Thomas L. Crisman (Hydrobiologia, 2003)

Behavioural response of plant-associated Eurycercus lamellatus (Ö.F. Müller) to different food sources and fish cues - Meryem Beklioglu; Erik Jeppesen (Aquatic Ecology, 1999)

The effects of tench (Tinca tinca (L.)) and sticklebacks (Gasterosteus aculeatus L.) on planktonic and benthic communities in mesocosms in a shallow lake - Meryem Beklioglu; Brian Moss (Aquatic Ecology, 1998)

Vertically-challenged limnology; contrasts between deep and shallow lakes - Brian Moss; Meryem Beklioglu; Laurence Carvalho; Sabri Kilinc; Suzanne McGowan; Deborah Stephen (Hydrobiologia, 1997)